Synthesis, physicochemical properties, and protective effects of a novel water-soluble tetrahydrocurcumin-diglutaric acid prodrug on ethanol-induced toxicity in HepG2 cells - Nattapong Jongjitphisut (2022)
Purpose: Tetrahydrocurcumin (THC) is a major reductive metabolite of curcumin that exhibits potent antioxidant effects; however, its pharmacological activities are limited by its poor water solubility. To overcome this, tetrahydrocurcumin-diglutaric acid (TDG), a novel water-soluble ester prodrug of THC, was synthesized and evaluated for its protective effects against ethanol-induced toxicity in liver cells. Methods: A simple esterification reaction was used to synthesize TDG. Physicochemical properties including water solubility, partition coefficient, chemical stability, and drug release were evaluated. The in vitro protective effects of TDG against ethanol-induced toxicity in HepG2 cells were evaluated on cell viability, reactive oxygen species (ROS) accumulation, oxidative stress, and apoptosis using MTT, DCFH-DA, antioxidant enzyme activity, and caspase activity assays, respectively. Results: TDG was successfully synthesized in good yield, and its chemical structure was confirmed via FT-IR, NMR, and high-resolution mass spectra. The solubility of TDG was greater than that of THC in phosphate buffer (pH 6.8) and able to release THC into the plasma. TDG exhibited protective effects by increasing cell viability compared with THC. Further studies on the hepatoprotective mechanisms revealed that TDG significantly reduced intracellular ROS compared with THC by restoring the antioxidant system (catalase, glutathione peroxidase, and glutathione levels). Moreover, TDG and THC inhibited apoptosis by modulating the activation of caspase-3 and -9. Conclusion: The results indicate that TDG represents a potential preclinical and clinical candidate for further hepatoprotective evaluation. Additionally, glutaric acid serves as a promoiety for conjugating bioactive molecules to enhance their water solubility and pharmacological effects.